THE ANALYSIS RELATED VARIATION SLICE THICKNESS TO IMAGE INFORMATION RECONSTRUCTION MAXIMUM INTENSITY PROJECTION (MIP) MSCT ABDOMINAL ANGIOGRAPHY IN THE HOSPITAL TELOGOREJO SEMARANG - Yeti Kartikasari; Nurdopo Baskoro; Muhammad Erfansyah; Anik Setyowati (Poltekkes Kemenkes Semarang, 2019)
The Research of this study was to determine the relationship of slice thickness to Maximum Intensity Projection (MIP) reconstructive image information and determine the exact slice thickness to the MIP processing of MSCT examination of Abdominal Angiography. Type of research is quantitative with an experimental approach, using a sample of 6 patients. Each patient performed a MIP reconstruction of the abdominal artery that is truncus coeliacs artery, gastric artery, hepatic artery, splenic artery, superior mesenteric artery, inferior mesenteric artery, renal artery, and communis iliac artery with variations in slice thickness of 5, 10, 15, 20 and 25 mm. Correlation test results produce a P-value= 0.001 smaller than α= 0.05 so that Ho is rejected and Ha is accepted, which means there is a relationship between slice thickness with image information on the MIP processing of abdominal arteries. Correlation coefficient value obtained is 0.593 so that the relationship obtained is moderate. The negative relationship is that the smaller the slice thickness, the diagnostic information on the abdominal artery is clearer, the greater the slice thickness, the diagnostic information generated is increasingly unclear. MIP reconstruction of the abdominal artery can produce clear image information on 5 mm and 10 mm.